2007
DOI: 10.1073/pnas.0611623104
|View full text |Cite
|
Sign up to set email alerts
|

PGC-1β controls mitochondrial metabolism to modulate circadian activity, adaptive thermogenesis, and hepatic steatosis

Abstract: The transcriptional coactivator peroxisome proliferator-activated receptor-␥ coactivator 1␤ (PGC-1␤) is believed to control mitochondrial oxidative energy metabolism by activating specific target transcription factors including estrogen-related receptors and nuclear respiratory factor 1, yet its physiological role is not yet clearly understood. To define its function in vivo, we generated and characterized mice lacking the functional PGC-1␤ protein [PGC-1␤ knockout (KO) mice]. PGC-1␤ KO mice are viable and fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
206
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(221 citation statements)
references
References 39 publications
11
206
4
Order By: Relevance
“…Mitochondrial biogenesis and respiration are highly dependent on the transcriptional coactivators, PGC-1α and β, and their interacting factors (Puigserver et al 1998;Wu et al 1999;Lehman et al 2000;Lin et al 2002;Kelly and Scarpulla 2004;Arany et al 2007;Sonoda et al 2007). In addition, many physiologic, hormonal and dietary cues are transduced into adaptive protein changes via the transcriptional coactivator PGC-1α.…”
Section: Pgc-1αmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial biogenesis and respiration are highly dependent on the transcriptional coactivators, PGC-1α and β, and their interacting factors (Puigserver et al 1998;Wu et al 1999;Lehman et al 2000;Lin et al 2002;Kelly and Scarpulla 2004;Arany et al 2007;Sonoda et al 2007). In addition, many physiologic, hormonal and dietary cues are transduced into adaptive protein changes via the transcriptional coactivator PGC-1α.…”
Section: Pgc-1αmentioning
confidence: 99%
“…ERRα is involved in many aspects of lipid metabolism, likely by mediating actions of PGC-1α and -β (Kamei et al 2003;Schreiber et al 2003;Schreiber et al 2004;RodriguezCalvo et al 2006;Sonoda et al 2007). In the mouse intestine, ERRα controls the ApoA-IV promoter and loss results in reduced uptake of lipids (Luo et al 2003;Carrier et al 2004).…”
Section: Errαmentioning
confidence: 99%
“…They increase mitochondrial energy production by inducing the expression of genes that regulate fatty acid oxidation and by increasing mitochondrial activity (Kamei et al, 2003;Lin et al, 2003;Meirhaeghe et al, 2003;St-Pierre et al, 2003). Moreover, mice lacking either PGC-1a or PGC-1b exhibit little to no effect on mitochondrial mass and respiration activity (Lin et al, 2004;Leone et al, 2005;Lelliott et al, 2006;Sonoda et al, 2007). However, RNAimediated down-regulation of PGC-1b in PGC-1a À/À preadipocyte lines additively inhibits mitochondrial respiration (Uldry et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…22 Similarly, knockout of PGC-1b, its homolog, results in abnormal circadian locomotor activity patterns. 23 Recently, Li et al 24 identified BAF60a as a partner for PGC-1a to regulate hepatic lipid metabolism in a genome-wide coactivation analysis. BAF60a is a subunit of the SWI/SNF chromatin-remodeling complexes that regulate nucleosome and chromatin structure through ATP hydrolysis.…”
mentioning
confidence: 99%